2021
DOI: 10.1080/13698249.2021.1903780
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Child Soldiers on Rebel Violence against Civilians

Abstract: Existing work describes child soldiers as very violent towards civilians. This implies that employing children should increase rebels' victimization of civilians. Challenging this, I posit that children's effect on group behaviour is conditioned by whether rebels' receive civilian support. Because they have weak pre-existing norms, children are prone to normalize violence but also likely to be susceptible to rebel efforts to control their use of violence. They should thus closely follow group rules in their be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Second, an ordinal measure that considered the scale of child recruitment within these conflicts per nonstate actor. This dataset provides scholars and policymakers alike with a comparative tool that is geographically diverse and has been used in numerous academic studies and policy reports since its release (e.g., Bakaki and Hinkkainen 2016, Haer and Böhmelt 2017, Faulkner et al 2019, Haer et al 2020, Faulkner and Doctor 2021, Mehrl 2021. Several extensions to the CSDS have since followed.…”
Section: Assessing Available Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, an ordinal measure that considered the scale of child recruitment within these conflicts per nonstate actor. This dataset provides scholars and policymakers alike with a comparative tool that is geographically diverse and has been used in numerous academic studies and policy reports since its release (e.g., Bakaki and Hinkkainen 2016, Haer and Böhmelt 2017, Faulkner et al 2019, Haer et al 2020, Faulkner and Doctor 2021, Mehrl 2021. Several extensions to the CSDS have since followed.…”
Section: Assessing Available Toolsmentioning
confidence: 99%
“…In addition to the individual-level effects, child recruitment also has direct implications on the dynamics of conflict and the post-conflict environment, influencing the stability of the entire region. For instance, recent research has suggested that child soldier recruitment contributes to the endurance and recurrence of armed conflicts (Haer andBöhmelt 2016, 2017) and increased violence against civilians within armed conflicts (Mehrl 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, I approximate this via mean ageand its squareas older fighters, on average, should have more combat experience. 17 Fourth, the CPN-M recruited substantial numbers of child soldiers and they may increase both combat effectiveness (Haer and Böhmelt, 2016) and violence against civilians (Mehrl, 2021). As command positions tend to be filled by male adults, largely restricting women and children to the rank-and-file (Henshaw et al, 2019), one may expect a threshold to women's and children's participation in a unit and their shares to thus be interrelated.…”
Section: Data and Empirical Strategymentioning
confidence: 99%
“…Finally, future researcher could unpack the indirect governance chain by not only considering the relationship between the state sponsor and the rebels, but also the relationship between rebel leadership and their soldiers (see, e.g., Weinstein 2005; Hoover Green 2016) as well as interactions between the different links in this chain (see, e.g., Mehrl 2020Mehrl , 2021. Future studies could also examine the impact of support modes on group cohesion (see also , Tamm 2016;K.…”
Section: Theoretical Implicationsmentioning
confidence: 99%